Punishment or Restoration: The role of group bias and harsh nurturing on children's preference (2025)
The preference for a retributive or restorative response to injustice has been a topic of interest in conflict resolution research. The role of group affiliation and parental practices in the development of a justice orientation preference remains unclear. The present study investigated 7- to 11-year-old (total n = 64) children's restoration behaviors when they were third-party bystanders of transgressions. In our experiment, after assigning the participants to a certain group affiliation condition (ingroup or outgroup), we showed stories through vignettes that portrayed a distributive transgression.